EFEKTIVITAS PEMANFATAAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM TERINTEGRASI SAINS UNTUK KELAS VIIA SMPN 38 SELUMA - Turiman Turiman (IAIN Bengkulu, 2020)
This study aims to determine the Effectiveness of Utilization of Teaching Islamic education Integrated Science Class VIIA SMPN 38 Seluma Kecamatan Sukaraja Seluma district academic year 2016 / 2017. This type of research is a developmen study with the respondents of class VIIA students SMPN 38 Seluma And using data collection techniques through question- naires from teachers, peers and expert tests after obtaining the data determined the level of validity by using a checklist. The results of this study indicate that the use of teaching materials of Integrated Islamic Studies of Science more effectively used in the learning process in comparison with previous teaching materials with a comparison of 18 students 38.88% (only 7 people are categorized pass) while 88.88% Material of Integrated Islamic Religion Science reaches 16 people who are categorized as graduated ).